2022
DOI: 10.1155/2022/2802636
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Modified Sang ju-Yin Decoction Combined with IFNαlb Nebulization on IL-1β and HBD2 in Children with Asthmatic Bronchitis

Abstract: Background. Breathing disease swelling of the lung tubes caused by viral infection is more and more likely to develop into related to the lung tubes breathing disease, especially repeating breathing loudly. Objective. To investigate the effect of modified Sang ju-Yin Decoction combined with Interferon (IFN)αlb nebulization on children with asthmatic bronchitis and the effects of IL-1β and β-defensin 2 (HBD2). Materials and Methods. The clinical data of 80 children with asthmatic bronchitis who were diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%